Fabrication of Mo/Co‐alumina‐coated kaolin‐based catalytic membrane for use in a catalytic membrane reactor. Issue 2 (18th July 2019) - Bose, Sujoy; Hazarika, Shyamoli; Das, Chandan
Abstract: In this research work, for the first time, the coating of Mo/Co‐alumina catalytic layer on kaolin‐based low‐cost tubular support was investigated. Molybdenum disulfide (MoS2 ) nanopowder (solid lubricant), silica gel (additive), and sodium metasilicate (binder) powder were used to synthesize appropriate lubricant solution for coating of the catalyst over the exterior surface of the ceramic support. Paint coating technique was adopted for simplicity, ease of methodology, and minimization of cost. The result showed that the lubricant solution containing silica gel and sodium metasilicate could not be used for the preparation of layers. However, the coating solution without silica gel and sodium metasilicate were completely stable, dispersible, and the fabricated layer distributed finely over the ceramic support. The prepared catalytic membrane had suitable porous and crack‐free microstructure with a desirable crystalline phase, indicating proper distribution and dispersion of catalyst over the support membrane surface. The removal or recovery of elemental sulfur using the fabricated catalytic membrane and membrane reactor (CMR) as a function of catalytic activity is also reported. Abstract : A new generation of the catalytic membrane has been obtained by a coating of the catalyst with the help of MoS2 additive material over kaolin‐based tubular ceramic support membrane.The dispersion of Mo/Co‐alumina catalyst‐MoS2 ‐based slurry along with binders and additives is caused by the formation of Si‐O‐(Na) asymmetric stretching vibrations, Mo‐S, and S‐S bands. The morphological structure and catalytic performance of the membrane are depending on the dispersion and distribution of catalyst over the membrane. An economically viable and commercially feasible catalytic membrane has been fabricated which can efficiently recover the sulphur from Claus gases (acid gas).